2020
DOI: 10.1021/acsami.9b14494
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide Film Saturable Absorber Based on Sol–Gel Glass and Spin-Coating Used in High-Power Q-Switched Nd:YAG Laser

Abstract: In recent years, many different kinds of nonlinear optical materials have been applied to passively Q-switched solid-state lasers. However, the average output powers of these lasers are typically limited to 1 W due to the low damage threshold of the materials. In this study, a molybdenum-disulfide-doped glass-composite absorber was synthesized using the sol−gel method and spin-coating technique. The optical damage threshold of the absorber reached 3.17 J/cm 2 . Saturation intensity, modulation depth, and nonsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Currently, SA mirrors fabricated from bulk crystals and commercial semiconductors have become prevalent in the generation of pulse lasers via Q-switching and mode-locking. 4 However, these traditional SA materials cannot entirely satisfy the current growing requirements because of their high cost, complex fabrication, 15 relatively low NLO susceptibility, and limited operation bandwidth. 4 Therefore, discovering new materials with low cost, ultrafast broadband optical response, and large optical nonlinearities is significant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, SA mirrors fabricated from bulk crystals and commercial semiconductors have become prevalent in the generation of pulse lasers via Q-switching and mode-locking. 4 However, these traditional SA materials cannot entirely satisfy the current growing requirements because of their high cost, complex fabrication, 15 relatively low NLO susceptibility, and limited operation bandwidth. 4 Therefore, discovering new materials with low cost, ultrafast broadband optical response, and large optical nonlinearities is significant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This method effectively solves the problem of material shedding and aging if the 2D material on the DF is directly exposed to the air and prevents the laser degradation caused thereby. In addition, our recent research found it has been confirmed that the component of sol–gel glass is amorphous silica, which has a thermal conductivity and refractive index similar to those of optical fibers, which can prevent materials in the air from aging or shedding and effectively increase damage threshold and long-term stability of the laser. , …”
Section: Introductionmentioning
confidence: 90%
“…In addition, our recent research found it has been confirmed that the component of sol−gel glass is amorphous silica, which has a thermal conductivity and refractive index similar to those of optical fibers, which can prevent materials in the air from aging or shedding and effectively increase damage threshold and long-term stability of the laser. 32,33 The optical properties of the SA are analyzed by a nonlinear transmission measurement. The results show that the saturation intensity and MD are 155.5 MW/cm 2 and 15.45% at 1.5 μm and 147.1 MW/cm 2 and 19.53% at 1.03 μm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a lot of 2D materials such as graphene, transition-metal dichalcogenides, MXene, , and perovskite materials , were employed as SA for the generation of ultrafast laser pulses. However, most of them have achieved either mode-locking or Q-switching operation. Only a few SAs are capable of generating mode-locked, Q-switched, and harmonic mode-locked pulses altogether for a specific waveband. Additionally, most 2D SAs demonstrated pulse laser generation in a single or two wavelength regimes. Meanwhile, studies on the SAs generating pulsed laser in three different wavelengths (1, 1.5, and 2 μm), covering the near-infrared to the mid-infrared regime, are still quite inadequate.…”
Section: Introductionmentioning
confidence: 99%